Potret Pendidikan Islam Kh. Hasyim Asy’ari Dan Implikasinya Pada Pendidikan Saat Ini - Muhidin, Firdaus (Peneliti.net, 2023)
Our generation has always been synonymous with violence, bad morals or morals, lack of self-confidence, no longer respecting teachers, and so on. This requires a new, young and fresh mindset that blends Islamic education, which at least is to fortify this bad behavior. One of them is Islamic education KH. Hasyim Asy'ari who colors education today. KH. Hasyim Asy'ari educates students as noble, ethical, religious, and ethical human beings. So this is the aim of the research to go deeper. The method used in this research is a qualitative type which is library research. The data studied were sourced from articles, journals, diaries and books related to the discussion, with references to the book KH. Hasyim Asy'ari is Adabul 'alim wal muta'allim, and other supporting references. Analysis of the data used is content analysis. The results obtained that Islamic education KH. Hasyim reminded the need to provide a special place for the existence of basic religious knowledge, such as aqidah, sharia, morals, Al-Qur'an, Hadith, and Arabic, so that students can have noble character, be religious, love each other, respect and obey. Besides that, Islamic education KH. Hasyim Asy'ari and his implications for education today are with the aim of forming good character having a rational, correct, comprehensive or perfect understanding of Islamic teachings and also being able to apply them in everyday life in an istigomah, committed, consistent manner. , as a human being who believes and fears Allah SWT. So that all actions, actions, and speech are based on the knowledge that has been obtained.